Good dirt eaudiobook A novel. - Wilkerson, Charmaine (Books on Tape, 2025)
NATIONAL BESTSELLER • The daughter of an affluent Black family pieces together the connection between a childhood tragedy and a beloved heirloom in this moving novel from the bestselling author of Black Cake, a Read with Jenna Book Club Pick “Engrossing . . . Wilkerson masterfully weaves these threads of love, loss and legacy [into] a thoroughly researched and beautifully imagined family saga.”— The New York Times When ten-year-old Ebby Freeman heard the gunshot, time stopped. And when she saw her brother, Baz, lying on the floor surrounded by the shattered pieces of a centuries-old jar, life as Ebby knew it shattered as well. The crime was never solved—and because the Freemans were one of the only Black families in a particularly well-to-do enclave of New England—the case has had an enduring, voyeuristic pull for the public. The last thing the Freemans want is another media frenzy splashing their family across the papers, but when Ebby's high profile romance falls apart without any explanation, that's exactly what they get. So Ebby flees to France, only for her past to follow her there. And as she tries to process what's happened, she begins to think about the other loss her family suffered on that day eighteen years ago—the stoneware jar that had been in their family for generations, brought North by an enslaved ancestor. But little does she know that the handcrafted piece of pottery held more than just her family's history—it might also hold the key to unlocking her own future. In this sweeping, evocative novel, Charmaine Wilkerson brings to life a multi-generational epic that examines how the past informs our present.